ADVANCING POLITICAL AND ECONOMIC INTERESTS THROUGH DATA LOCALIZATION IN THE NAME OF PRIVACY AND SECURITY - Sargsyan, Tatevik (AoIR Selected Papers of Internet Research, 2015)
Revelations about the US National Security Agency’s mass surveillance programs presented an opportunity for foreign governments to push forward their Internet governance agenda. Many nation states proposed infrastructure-based initiatives to localize data within their jurisdiction citing concerns over privacy and security of their citizens. Relying on a conceptual framework that connects Internet infrastructure to power and social control this paper examines data localization proposals by a number of governments arguing that their purpose is to pursue alternative political and economic objectives in the name of privacy and security.